Determinants of customer satisfaction and customer loyalty : exploring the moderating role of switching cost and customer experience among Malaysian postpaid mobile phone users - Syukrina Alini Mat Ali
The mobile network service within the telecommunications industry has a good potential to increase in growth. However, market saturation has caused the growth rate of mobile network subscribers in developing countries to slow down. Hence, it is a challenge for service providers to retain and gain loyalty, as the competition among them is severed. Even though customers are satisfied with their service providers, they may still turn away to other competitors. Therefore, it is important to highlight on the issue on customer loyalty as it is still challenging to understand the context of customer loyalty in the service industry due to the higher expectation of the subscribers. Thus, there is a need to integrate and consolidate the possible variables in order to understand better on customer loyalty. Therefore, this study further clarifies on customer loyalty by investigating the influence of service expectation, service confirmation and perceived service performance towards satisfaction. This study further examined the relationship between satisfaction and loyalty. The moderating roles of switching cost and customer experience were also assessed in this study. A positivist exploratory approach was used to explore the relationship between variables. Convenience sampling technique was employed and based on 338 usable data gathered from Maxis, Digi and Celcom post-paid subscribers in Kuala Lumpur, the data was analyzed using Partial Least Square – Structural Modelling (PLS-SEM) approach. The findings revealed that all relationship between constructs were significant including the moderating role of switching cost and customer experience. However, insignificant result was found on the relationship between service expectation and satisfaction. This research provides insight into determinants of customer loyalty among post-paid subscribers in Malaysia. The major theoretical contributions of this study include extending the previous literature on customer loyalty from the perspective of expectation and perceived service performance. The findings further extend the current stock of knowledge by examining the influence of switching cost and customer experience in the existing expectations confirmation theory. From practical viewpoint, the findings provided information for the telecommunication industry to develop certain strategies to improve and enhance customer satisfaction and loyalty among the subscribers. However, this study is subjected to several limitations. The approach of this study was deductive in nature, which limits the researcher's understanding of what is really happening in telecommunication industry. Therefore, further efforts should be placed on examining the determinants of customer loyalty from qualitative perspectives.